2020
DOI: 10.1093/dote/doaa094
|View full text |Cite
|
Sign up to set email alerts
|

Clinical benefits of a swallowing intervention for esophageal cancer patients after esophagectomy

Abstract: Summary Dysphagia after esophagectomy is the main cause of a prolonged postoperative stay. The present study investigated the effects of a swallowing intervention led by a speech–language–hearing therapist (SLHT) on postoperative dysphagia. We enrolled 276 consecutive esophageal cancer patients who underwent esophagectomy and cervical esophagogastric anastomosis between July 2015 and December 2018; 109 received standard care (control group) and 167 were treated by a swallowing intervention (inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…The start of oral intake was considered after confirmation that there were no major complications on the CT scan, and a step up in diet levels and initiation of drinking water were allowed based on comprehensive judgment on each patient's progress. 22 Patients were considered for discharge if a full caloric oral diet was tolerated, and physical strength allowed personal autonomy.…”
Section: Surgical Procedures and Perioperative Managementmentioning
confidence: 99%
“…The start of oral intake was considered after confirmation that there were no major complications on the CT scan, and a step up in diet levels and initiation of drinking water were allowed based on comprehensive judgment on each patient's progress. 22 Patients were considered for discharge if a full caloric oral diet was tolerated, and physical strength allowed personal autonomy.…”
Section: Surgical Procedures and Perioperative Managementmentioning
confidence: 99%
“…Three studies with a combined total of 311 participants who underwent oesophagectomy with thoracoscopy met inclusion criteria [ 37 , 69 , 70 ]. All three studies evaluated the impact of exercise-based dysphagia interventions on swallow related outcomes in adults with oesophageal cancer.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining 5 cases had no relevant co-morbidities that may affect swallowing NI Thoracic “Oesophagectomy” RLNP ( n = 5. 1 of which was bilateral resulting in severe AP) Non-validated: VFSS rating tool suggested by Logemann, 1998 Takatsu et al, 2020 [ 70 ] Retrospective case control study Aichi Cancer Centre Hospital, Japan 276 CG; median 68 (IQR 64–74) TG; 69 (IQR 62–73) CG: 91/18 M:F TG: 142/25 M:F NI TNM Classification (UICC) -I/II CG: 49 (45%) TG: 56 (45%) -III/IV CG: 60 (55%) TG: 91 (55%) Thoracic CG: Neoadjuvant therapies: 87 (80%) Thoracoscopic oesophagectomy Open Oesophagectomy Cervical anastomosis TG: Neoadjuvant therapies: 133 (80%) Thoracoscopic oesophagectomy Open oesophagectomy Cervical anastomosis CG: RLNP 22 (20%) Pneumonia 25 (23%) AL: 8 (7%) TG: RLNP 34 (20%) Pneumonia 39 (23%) AL 22 (13%) 1. Start of oral intake 2.…”
Section: Resultsmentioning
confidence: 99%
“…Kinematic analyses have shown that there are changes to hyoid movement and location of the epiglottis after esophagectomy that affect swallowing (14). Rehabilitation programs which are instituted early after esophagectomy can alleviate these disorders, however (15).…”
Section: Left Crus Right Crusmentioning
confidence: 99%